JMJD3 deficiency disturbs dopamine biosynthesis in midbrain and aggravates chronic inflammatory pain - Xi-Biao He; Fang Guo; Wei Zhang; Jiacheng Fan; Weidong Le; Qi Chen; Yongjun Ma; Yong Zheng; Sang-Hun Lee; Hui-Jing Wang; Yi Wu; Qinming Zhou; et al. (Acta Neuropathologica Communications)
Abstract Midbrain dopamine (mDA) neurons participate in a wide range of brain functions through an intricate regulation of DA biosynthesis. The epigenetic factors and mechanisms in this process are not well understood. Here we report that histone demethylase JMJD3 is a critical regulator for DA biosynthesis in adult mouse mDA neurons. Mice carrying Jmjd3 conditional knockout or undergoing pharmaceutical inhibition of JMJD3 showed consistent reduction of DA content in midbrain and striatum. Histological examination of both mice confirmed that TH and NURR1, two key molecules in DA biosynthesis pathway, were decreased in mDA neurons. Mechanistic experiments in vivo and in vitro further demonstrated that the transcriptions of Th and Nurr1 in mDA neurons were suppressed by JMJD3 deficiency, because of increased repressive H3K27me3 and attenuated bindings of JMJD3 and NURR1 on the promoters of both genes. On behavioral level, a significant prolonged inflammation-induced mechanical hyperalgesia was found in conditional knockout mice regardless of sex and age, whereas motor function appeared to be intact. Our findings establish a novel link between DA level in mDA neurons with intrinsic JMJD3 activity, and suggest prolonged chronic inflammatory pain as a major loss-of-function consequence.